Numerical Modelling of a Photovoltaic Thermal (PV/T) System Using Nanofluid With Parallel Flow Thermal Absorber. Issue 1 (December 2021) - Kubenthiran, J.; Baljit, S.; Tijani, A. S.; Baharin, Z. A. K.; Remeli, M.F.; Ong, K. S.
Abstract: In the present study, a numerical model of photovoltaic thermal (PV/T) system using alumina (Al2 O3 ) nanofluid, and pure water are used as working fluid. The proposed PV/T model consists of parallel riser tubes that are connected to two header tubes and it is attached to an absorber plate to simulate the conduction and convection heat transfer mechanism of a conventional PV/T system. The energy efficiency of the PV/T model is analyzed by varying the solar radiation (Heat Flux), inlet fluid velocity, and the volume percentage of the nanofluids. The numerical simulation is performed by using a conjugate heat transfer method with a computational fluid dynamics (CFD) software. According to the simulation data, the energy efficiency and the heat transfer coefficient of the PV/T system increased by increasing the inlet fluid velocity. In comparison with water, alumina nanofluid showed better thermal and electrical efficiency due to its high thermal conductivity. The thermal efficiency increased by 5.55% for alumina, compared to pure water and the electrical efficiency increased by 0.15% for alumina. Moreover, the effect of inlet fluid velocity ranging from 0.04m/s to 0.2m/s was also evaluated, and the results showed that the increase in thermal efficiency for pure water and alumina are 18.15% and 25.77%, respectively. Subsequently, the electrical efficiency increased by 0.52% and 0.56% for pure water and alumina using the new parallel flow thermal absorber, respectively.